Light transmittance performance of sustainable translucent self-compacting concrete. (June 2021) - Tahwia, Ahmed M.; Abdel-Raheem, Ahmed; Abdel-Aziz, Nirmen; Amin, Mohamed
Abstract: Translucent self-compacting concrete (TSCC) is an innovative energy-saving construction material. TSCC was prepared by Portland cement, limestone powder, silica fume, coarse aggregate, fine aggregate, water, superplasticizer, and plastic optical fibers (POF) to allow inward sunlight transmission. This research investigates the compressive strength as well as the natural and artificial light transmittance performance of TSCC containing different POF volume ratios and diameters. The natural light transmittance performance investigated at natural light conditions from 7 a.m. to 7 p.m. The artificial light transmittance performance was analyzed at voltage variation, light source variation, using a group of light-dependent resistors (LDRs) instead of single LDR and varying the distances from light source to specimen. TSCC was also compared with that of translucent self-compacting mortar (TSCM) and it was found that the artificial light transmittance performance of TSCC was somewhat similar to that of TSCM. The experimental study showed that although the compressive strength increased with increasing POF volume ratios and diameters, the light transmittance significantly increased in a direct quadratic relationship with increasing POF volume ratios. In this research, TSCC performs up to 21.35% and 24.7% of natural and artificial light transmittance near-cube face, respectively, which is enough lighting for commercial and residential buildings. Highlights: Effect of design factors on light transmittance performance of TSCC. Natural and artificial light transmittance performance are investigated. Increasing the POF volume ratio significantly increases the light transmittance. Increased POF volume ratios and diameters enhances compressive strength.